Activation of the hypothalamic-pituitary adrenal axis in response to a verbal fluency task and associations with task performance - Becker, Linda; Schade, Ursula; Rohleder, Nicolas (PLoS ONE, 2020)
Speech fluency can be impaired in stressful situations. In this study, it was investigated whether a verbal fluency task by itself, i.e. without the presence of any further stressors, induces responses of the hypothalamic-pituitary adrenal (HPA) axis and of the sympathetic nervous system (SNS). The sample consisted of n = 85 participants (68.2% female; 33.3 ± 15.2 years) who performed two consecutive verbal fluency tasks for two minutes each. The categories were either ‘stress’ or ‘disease’ and ‘animals’ or ‘foods’ which were presented in a randomized order. Three saliva samples were collected, prior to the task (t0), immediately after (t1), and ten minutes after it (t2). Salivary α-amylase and cortisol were assessed. Furthermore, blood pressure, heart rate, and ratings of actual stress perception, level of effort, and tiredness were measured. The verbal fluency task induced a HPA axis response with a maximum cortisol level at t2 which was independent of task performance. Furthermore, perceived stress and effort, as well as tiredness increased after the task. Moreover, tiredness immediately after the task was negatively correlated with task performance. No α-amylase, blood pressure, or heart rate, and therefore SNS, responses were found. Implications for the integrated specificity model are discussed. We conclude that a verbal fluency task acts like an acute stressor that induces a cortisol and a perceived stress response without the need for further (e.g., social-evaluative) stress components. Therefore, it is a less time-consuming alternative to other stress tasks that can be used in field studies with little effort.<br
Keywords: stress response; stress task; verbal fluency; speech fluency; hypothalamic-pituitary adrenal axis; sympathetic nervous system; cortisol; α-amylase; blood pressure; heart rate